2016
DOI: 10.1002/ece3.2474
|View full text |Cite
|
Sign up to set email alerts
|

Mating and longevity in ant males

Abstract: Across multicellular organisms, the costs of reproduction and self‐maintenance result in a life history trade‐off between fecundity and longevity. Queens of perennial social Hymenoptera are both highly fertile and long‐lived, and thus, this fundamental trade‐off is lacking. Whether social insect males similarly evade the fecundity/longevity trade‐off remains largely unstudied. Wingless males of the ant genus Cardiocondyla stay in their natal colonies throughout their relatively long lives and mate with multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 33 publications
(37 reference statements)
0
17
0
Order By: Relevance
“…Despite the accumulation of evidence that a strong allocation to sperm production can entail acute physiological costs, its long‐term consequences in terms of lifespan or survival ageing have been largely overlooked. Yet, some studies performed on insects have revealed that high mating rates can shorten male lifespan (Partridge and Farquhar, 1981; Martin and Hosken, 2004; Paukku and Kotiaho, 2005; Dao et al ., 2010; Metzler et al ., 2016; Jehan et al ., 2020), which might be due to the down‐regulation of the expression of some specific genes (e.g. metabolic genes) straight after sexual activity (Branco et al ., 2017).…”
Section: Ageing Costs Of Sperm Competitionmentioning
confidence: 99%
“…Despite the accumulation of evidence that a strong allocation to sperm production can entail acute physiological costs, its long‐term consequences in terms of lifespan or survival ageing have been largely overlooked. Yet, some studies performed on insects have revealed that high mating rates can shorten male lifespan (Partridge and Farquhar, 1981; Martin and Hosken, 2004; Paukku and Kotiaho, 2005; Dao et al ., 2010; Metzler et al ., 2016; Jehan et al ., 2020), which might be due to the down‐regulation of the expression of some specific genes (e.g. metabolic genes) straight after sexual activity (Branco et al ., 2017).…”
Section: Ageing Costs Of Sperm Competitionmentioning
confidence: 99%
“…In male insects, the longevity costs of mating have been well-described thanks to experiments manipulating the male reproductive energy expenditures (see [ 52 ] for a review of empirical evidence). For example, in the social ant species Cardiocondyla obscurior , males experimentally assigned to a ‘high mating rate’ treatment showed a reduced lifespan by approximately 35% compared to that of males assigned to a ‘low mating rate’ treatment, with a result interpreted as a possible trade-off between reproductive energy expenditure (i.e., in spermatogenesis and/or courtship behaviour) and somatic maintenance [ 73 ]. Such mating costs have also been reported in wild populations of antler flies ( Protopiophila litigata ) in which long-lived males had a lower mating rate [ 74 ].…”
Section: Sex Gap In Aging and Longevity As A Side-effect Of Sexual Sementioning
confidence: 99%
“…In insects, there may be a trade-off between mating and survival, as their longevity tends to decrease as the mating frequency increases (Oliver and Cordero 2009, Metzler et al 2016). This trade-off may not exist for some insects (Camacho-Garcia et al 2018).…”
Section: Discussionmentioning
confidence: 99%